Effect of non-surgical periodontal therapy on serum ferritin levels in postmenopausal women with chronic periodontitis - Masoumeh Faramarzi; Adileh Shirmohammadi; Azin Khorramdel; Mehrnoosh Sadighi; Elshan Bargahi (Tabriz University of Medical Sciences, 2021)
Background. Ferritin is a positive acute phase protein (APP) in inflammation and chronic infections, including chronic periodontitis. Two key factors that can regulate ferritin expression are iron and pro-inflammatory cytokines. Serum ferritin levels increase after menopause, affecting women's health. This study aimed to evaluate serum ferritin levels in postmenopausal women upon undertaking non-surgical periodontal treatment. Methods. In this cross-sectional study, blood samples of 38 postmenopausal women with chronic periodontitis were collected before any treatment. The serum ferritin levels and periodontal parameters, probing depth (PD), clinical attachment level (CAL), and gingival index (GI) were recorded at baseline and three months after non-surgical periodontal therapy. Wilcoxon test was used to compare serum ferritin levels before and after treatment. T-test was used for comparison of periodontal parameters, with a P value of ≤0.05 considered significant. Results. A decrease was observed in the serum ferritin level (from 108.55 mcg/L to 98.28 mcg/L) after treatment compared to baseline (P<0.001). Also, significant improvements in periodontal parameters were observed compared to the baseline (P<0.001). Conclusion. Based on the results, it can be concluded that non-surgical periodontal treatment significantly reduces serum ferritin levels in postmenopausal women with chronic periodontitis.